2011
DOI: 10.1016/j.cell.2011.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Linking RNA Polymerase Backtracking to Genome Instability in E. coli

Abstract: SUMMARY Frequent co-directional collisions between the replisome and RNA polymerase (RNAP) are inevitable because the rate of replication is much faster than that of transcription. Here we show that the outcome of such collisions depends on the productive state of transcription elongation complexes (ECs). Co-directional collisions with backtracked (arrested) ECs lead to DNA double strand breaks (DSBs), whereas head-on collisions do not. A mechanistic model is proposed to explain backtracking-mediated DSBs. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
449
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(459 citation statements)
references
References 60 publications
8
449
1
1
Order By: Relevance
“…A major source of nucleoprotein replicative barriers is transcription, with mutations within RNA polymerase subunits being able to suppress multiple defects in genome duplication (20,(32)(33)(34). One such mutation, rpoB [H1244Q], suppresses defects in genome duplication by reducing the stability of stalled transcription complexes (20) and inhibiting backtracking of RNA polymerase (35). We found that this mutation suppressed the RecD2-dependent killing of Δrep cells as evinced by colony-forming ability (Fig.…”
Section: Clearance Of Nucleoprotein Barriers Ahead Of Forks Protects mentioning
confidence: 76%
“…A major source of nucleoprotein replicative barriers is transcription, with mutations within RNA polymerase subunits being able to suppress multiple defects in genome duplication (20,(32)(33)(34). One such mutation, rpoB [H1244Q], suppresses defects in genome duplication by reducing the stability of stalled transcription complexes (20) and inhibiting backtracking of RNA polymerase (35). We found that this mutation suppressed the RecD2-dependent killing of Δrep cells as evinced by colony-forming ability (Fig.…”
Section: Clearance Of Nucleoprotein Barriers Ahead Of Forks Protects mentioning
confidence: 76%
“…Even spurious transcription elicited by rho inactivation is not necessarily catastrophic, as observed for B. subtilis (Nicolas et al, 2012), although condition-dependent or long-term effects may not be readily detected. For instance, genome instability may arise from uncontrolled encounters between transcription and replication machineries, since Rho inactivation should favour their codirectional collisions and the resultant formation of DNA double-strand breaks (Dutta et al, 2011). Traffic control may also explain why Rho is sometimes more important or abundant under conditions such as cold (Mykytczuk et al, 2011;Piette et al, 2010;Quirk et al, 1993) that favour formation (and thus require clearance) of roadblocks such as arrested RNA polymerases and R-loops (Erie, 2002;Massé & Drolet, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…They include control of faithful gene expression [e.g. by transcriptional polarity (Ciampi, 2006;Peters et al, 2011)], regulation of specific genes/operons in response to environmental cues [notably through riboswitch-and small RNA-dependent mechanisms (Bossi et al, 2012;Hollands et al, 2012)], prevention of spurious transcription (Cardinale et al, 2008;Peters et al, 2009Peters et al, , 2012 and of R-loop formation (Krishna Leela et al, 2013), and roles in maintenance of genome integrity (Dutta et al, 2011;Washburn & Gottesman, 2011). These functions rely more-or-less directly on Rho cooperating with various endogenous factors.…”
Section: Introductionmentioning
confidence: 99%
“…If not resolved through hydrolysis, backtracked complexes form temporary obstacles for other RNAPs and the replication fork, which may be detrimental to cells (unpublished) (Dutta et al, 2011). In addition, further extension in misincorporated complexes would lead to erroneous transcripts.…”
Section: Replacement Of the Tl By Transcription Factors And Switchingmentioning
confidence: 99%